Is there any alternative to the confiscation of criminal assets, which is implemented in a criminal proceeding? - Lajić, Oliver N (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In addition to confiscation of proceeds of crime in the criminal or its associate procedure, as exists in national law, the author suggests the existence of other models in the seizure of property whose legal origin is suspected, represented in foreign legal systems. Recognizing this fact, the central part of his work is about the civil law confiscation or seizure of proceeds of crime in the administrative proceedings and taxing criminal profit, as alternative or corrective forms of action present in comparative legal systems. Briefly has been given an overview of basic principles on which they are based, and pointed out the problems faced by entities engaged in the field of their practical application. After a brief presentation and analysis of these systems the author raises a rhetorical question: whether the use of civil law or administrative proceedings legitimate tool in the fight against crime or a shortcut that states use to mitigate the lack of efficiency of the instruments used in crime fighting? In doing so, he reminds that confiscation and forfeiture and the criminal or its associated procedure is exactly the kind of civil law Institute (prohibiting unjust) used in the realization of the goals of the criminal law. Essentially, it is a desirable tool, which can help to achieve (partial) restorative justice. However, putting discussed aspects of confiscation in the view of the domestic law, the author concludes that the decision which has been opted by domestic legislator is currently the best way for the practical implementation of the principle of prohibition of unlawful enrichment. keywords: confiscation of criminal assets, criminal proceeding, civil proceeding, administrative proceeding